The role of clinical pathway on the outcomes of ischemic stroke patients at Bethesda Hospital Yogyakarta - Rizaldy Pinzon, Francisca Diana Alexandra Iwan Dwiprahasto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Stroke becomes world health problem all over the world because it is the causal factor of high mortality and disability. Good and well-organized process of healthcare service will improve the outcome of the patients with stroke. Clinical pathway may be used as clear standard to help reduce unnecessary variations of medical treatment and measure. The study aimed at finding out the correlation between the use of clinical pathway and the outcome of the patients with ischemic stroke in Bethesda Hospital Yogyakarta. It was an observational and analytic study with cohort restorative study design. The author compared the outcomes of acute ischemic stroke between the group with clinical pathway and the group without the clinical pathway. Data was collected using consecutive sampling from the electronic registry and medical record data of the patients from January 1st, 2011 to December 31st, 2011. It was conducted to 124 patients with ischemic stroke assigned to two groups (the first groups of 62 patients with clinical pathway and the second groups of 62 patients without clinical pathway). The basic characteristics of the two groups were the same. The results of the analysis showed that there was a significant decrease in the incidence of complication and a significant increase in the use of antiplatelete drugs, antidiabetic drugs and statin as secondary preventive measure of the recurrent stroke. There was not any significant difference in the duration of the hospitalized healthcare, the financing and the mortality between the two observation groups. The study indicated that the use of the clinical pathway in the stroke treatment improved the outcome of the patients with stroke. It was necessary to conduct further study to evaluate the effectiveness of the clinical pathway in improving the outcome of the patients with bigger number of the subjects and the longer period of time.Â Keywords: clinical pathway - stroke - outcomesÂ Â